Eco-epidemiological analysis of Rickettsia parkeri in domestic dogs and Amblyomma ovale ticks in the Atlantic rainforest of Northeast Brazil - Michellin Pereira de Albuquerque; Mauricio Claudio Horta; Daniele Rosa Xavier de Melo; Gabriela Akemi Cardoso Gagliardi Takeda; Ana Isabel Arraes-Santos; Thiago Fernandes Martins; Adriano Pinter (Revista Brasileira de Parasitologia Veterinária)
Abstract In Brazil, spotted fever (SF) is caused by two species of Rickettsia, both of which are transmitted by Amblyomma ticks: Rickettsia rickettsii, which results in severe and often fatal cases, and Rickettsia parkeri, which causes a mild illness. This study focused on R. parkeri in Amblyomma ovale ticks from the Maciço de Baturité region, Ceará, Northeast Brazil, an area endemic for SF with mild symptoms. We examined 60 domestic dogs with access to the forest for ticks and Rickettsia seroprevalence. A landscape analysis was conducted in all forest patches within 2–10 km from the main forest edge. In total, 125 A. ovale ticks were collected from 30 dogs (50%). DNA from 65 ticks was tested using genus-specific Rickettsia primers. Three (4.6%) tick specimens tested positive for R. parkeri while the Rickettsia seroprevalence among the dogs was 55% (33/60). A probable occurrence of Rickettsia transmission was observed in the fragmented Atlantic rainforest, which has 1,019 ha of preserved land and 50.6 km of perimeter border. The land's characteristics allow for semi-domiciled dogs to access forest fragments, where A. ovale ticks are commonly present. Infected ticks may parasitize the dogs, which then transport the ticks into homes, potentially transmitting SF-causing bacteria to humans.